2020
DOI: 10.5802/smai-jcm.62
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter Estimation in Bayesian MAP Estimation: Parameterizations and Consistency

Abstract: The Bayesian formulation of inverse problems is attractive for three primary reasons: it provides a clear modelling framework; means for uncertainty quantification; and it allows for principled learning of hyperparameters. The posterior distribution may be explored by sampling methods, but for many problems it is computationally infeasible to do so. In this situation maximum a posteriori (MAP) estimators are often sought. Whilst these are relatively cheap to compute, and have an attractive variational formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Finally, we choose an annealing schedule š›½ ā„Ž such that š›½ ā„Ž šœ– 2 ā„Ž ā†’ 0, ensuring that Assumption (iii) holds. Specifically, we may choose š›½ ā„Ž āˆ¼ šœ– āˆ’1 ā„Ž , as suggested by (11) to obtain an approximation with the claimed quantitative convergence rate.…”
Section: Example: Transportation Networkmentioning
confidence: 99%
“…Finally, we choose an annealing schedule š›½ ā„Ž such that š›½ ā„Ž šœ– 2 ā„Ž ā†’ 0, ensuring that Assumption (iii) holds. Specifically, we may choose š›½ ā„Ž āˆ¼ šœ– āˆ’1 ā„Ž , as suggested by (11) to obtain an approximation with the claimed quantitative convergence rate.…”
Section: Example: Transportation Networkmentioning
confidence: 99%
“…They also provide a natural means of approximating general measures in the sense of weak convergence. Specifically, we consider a sequence of material likelihood measures Āµ D,h of the form given in (5). We begin by showing that, if (Āµ Ī² h ) is uniformly bounded and tight and (Āµ D,h ) suitably approximates Āµ D , then (Āµ h,Ī² h ) is also uniformly bounded and tight.…”
Section: 2mentioning
confidence: 99%
“…We begin by showing that, if (Āµ Ī² h ) is uniformly bounded and tight and (Āµ D,h ) suitably approximates Āµ D , then (Āµ h,Ī² h ) is also uniformly bounded and tight. (5). Let Ī² h ā†’ +āˆž and h ā†’ 0.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In their experiments, which included nonstationary hyperparameters, they concluded that using a hierarchical approach with a non-centered parameterization was significantly better than a hierarchical approach with a centered parameterization and bothh hierarchical approaches were better than a non-hierarchical approach. Subsequently, Dunlop et al Dunlop et al (2020) showed that for MAP estimation of the hyperparameters in a linear inverse problem, the centered parameterization is to be preferred when the goal is MAP estimation as opposed to uncertainty quantification.…”
Section: Introductionmentioning
confidence: 99%